Towards net-zero: CO2 capture and biogas purification through electric potential swing desorption to achieve SDGs 7 and 13 - Farooq, Muhammad; Rehman, Ateekh Ur; Anwer, Izza; Imran, Muhammad; Pettinau, Alberto; Andresen, John M. (Frontiers in Energy Research, 2023)
Currently, the potential of bio-methane derived from biogas is substantial, positioning it to fulfil a considerable share of the United Kingdom's total energy needs. The primary challenge associated with raw biogas lies in purifying it to produce bio-methane, a process that necessitates the removal of carbon dioxide and hydrogen sulphide. Among the various methods, activated carbon (AC) adsorption stands out as a particularly effective and costefficient approach for converting biogas into bio-methane, provided that the regeneration of AC proves economically viable. In this research, a segment of activated carbon was utilized to assess the adsorption properties when exposed to a gas mixture of CO2, H2S, and N2 within a regenerative activated carbon setup. This investigation encompassed the analysis of adsorption and desorption behaviours, process capacities, and the impact of regeneration. To enhance the adsorption of CO2, electro conductive polymers (ECP) were incorporated into the AC samples, leading to an extension in breakthrough time. Subsequent to adsorption, a novel method called electric potential swing desorption (EPSD) was employed for in-situ regeneration of activated carbon samples, involving potentials of up to 30V.The findings exhibited that the newly introduced EPSD technique considerably diminished desorption durations by 70-80% for both H2S and CO2. Moreover, it successfully rejuvenated the accessible adsorption sites, resulting in reduced desorption times compared to the initial breakthrough time during adsorption. Consequently, the ESPD system proves to be a promising candidate for in-situon-site regeneration of activated carbons to eliminate CO2 and H2S from biogas. Notably, this approach offers inherent advantages over conventional methods includinglike thermal swing adsorption (TSA) and pressure swing adsorption (PSA) in terms of regeneration. The demonstrated method underscores the potential for more efficient and economically viable cycles of adsorption and desorption, thereby enhancing the overall biogasto-bio-methane conversion process to achieve SDGs 7 and 13 for clean and green energy applications.